Aktivitas Antioksidan Senyawa Flavonoid Terprenilasi dari Ekstrak Diklorometana Daun Artocarpus communis - PUSPA D.N. LOTULUNG; SOFA FAJRIAH; EUIS FILAILA (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
This research investigated the antioxidant activity of prenylated flavonoid compound from the ichloromethane extract of Artocarpus communis leaves on 1,1-diphenyl-2-picryl hydrazyl free radicals scavenging assay. The dichoromethane extract of Artocarpus communis leaves was fractionated by column chromatography techniques on silica gel, and each fraction was assayed for its activity. The active compound, 1-(2,4-dihydroxyphenyl)-3-[8-hydroxy-2-methyl-2-(4-methyl-3-pentenyl)-2H-1-benzopyran-5-yl] 1-propanone, showed moderate antioxidant activity with IC50 54.6 μg mL-1.